2015
DOI: 10.1017/s1368980015001226
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control in pregnancy is associated with pre-conception dietary patterns

Abstract: Objective: To examine pre-conception dietary patterns in pregnant asthmatic women and to identify associations between maternal diet and asthma control during pregnancy. Design: Cross-sectional study. Pre-conception food frequency data were collected retrospectively. Asthma control was assessed using the Global Initiative for Asthma guidelines. Dietary patterns were derived using factor analysis. Binary logistic regression analyses were used to test the association between uncontrolled asthma and each dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
1
17
0
2
Order By: Relevance
“…This may be due to a difference in other risk factors such as smoking between obese and overweight women. Furthermore it may also be related to dietary intake in this population as we have reported recently that asthmatic women who consumed a diet high in fat, sugar and refined grains were twice as likely to have uncontrolled asthma during pregnancy regardless of BMI [29]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a difference in other risk factors such as smoking between obese and overweight women. Furthermore it may also be related to dietary intake in this population as we have reported recently that asthmatic women who consumed a diet high in fat, sugar and refined grains were twice as likely to have uncontrolled asthma during pregnancy regardless of BMI [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Poor dietary intake, such as foods high in saturated fats and glucose, contribute to inflammation through pathways involved in oxidative stress and insulin resistance, while foods high in antioxidants (such as fruits and vegetables) or unsaturated fatty acids (such as fish and nuts) are anti-inflammatory [24,25]. In keeping with these dietary effects on inflammation, a high fat/sugar/takeaway dietary pattern was associated with an increased likelihood of uncontrolled asthma in pregnancy [26]; and a high fat intake increased neutrophilic airway inflammation in subjects with asthma [27]. Higher dietary antioxidant intake was associated with improved lung function and asthma control (reviewed in [28]).…”
Section: Introductionmentioning
confidence: 99%
“…[8,[32][33][34][35] Dietary patterns analyses consider the totality of a diet and enables the data collected from observational studies to be translated into descriptions of eating behaviors that can inform public health guidelines and recommendations. [36] In this study, the variance in food intake explained by the dietary patterns was similar to the variance explained by the dietary patterns of a group of 327 pregnant women from the Rio de Janeiro, Brazil (25.3%) [20] Higher adherence to dietary patterns consisting of discretionary food items in the prepregnancy period has been linked with negative outcomes for both mother and child, [20] including maternal uncontrolled asthma, [38] gestational diabetes mellitus, [39] preterm delivery, [40] earlier gestation and shorter birth length. [40] However, these same kind of prepregnancy dietary patterns have not been shown to be associated with hypertension [41] nor depressive symptoms [32] in pregnancy, nor with early fetal growth[33] emphasizing the necessity for more studies in this field.…”
Section: Discussionsupporting
confidence: 60%
“…The explained variances found in the dietary pattern analyses in both studies have been well accepted in the field of nutritional epidemiology. [37][38][39] A study review on 54 papers describing maternal dietary patterns and pregnancy outcomes verified that the patterns were frequently classified as prudent or healthy (healthful, health conscious, fruit and low-fat dairy, cooked vegetables, high-protein/fruit, Mediterranean), traditional (common-Brazilian, Nordic, Southern), or as Western or processed (meats/snacks/sweets, high-fat/sugar/takeaway, junk, snack). The majority of the studies identified by the mentioned review study used FFQs to measure the dietary intake and applied principal component analysis to derive the dietary patterns.…”
mentioning
confidence: 99%